Taxing investments in the Asia-Pacific region: The importance of cross-border taxation and tax incentives - Verena Wiedemann; Katharina Finke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper investigates the taxation of investments in the Asia-Pacific region. Our analysis is based on the methodology of Devereux and Griffith (1999, 2003) for determining effective average tax rates. This approach allows us to account for important national and international tax regulations. Our results show that the overall dispersion of effective tax burdens in Asia-Pacific ranges from 10.6% in Hong Kong to 40.4% in India for domestic investments (overall average of 23.4%). In 8 out of 19 jurisdictions covered, investments are, however, effectively taxed at a rate between 20% and 25%. If the investment is made by a foreign investor, cross-border taxation has a significant impact on the overall tax burden. In any of the Asia-Pacific jurisdictions, foreign direct investments by a Singaporean or a German parent company are on average taxed at 29.2% and at 32.8% in case of a US investor. Meanwhile, tax incentives for the stimulation of private investment reduce the effective average tax rate by 8.6 percentage points on average. Fiscal incentives targeted at investments in the high technology sector or the development of specific geographic areas result in the lowest effective tax burdens.
urn:nbn:de:bsz:180-madoc-388182
Keywords: 330; Corporate Taxation; Effective Average Tax Rate; Tax Incentives; Asia